THE EFFECTIVENESS OF TEST STRIPS FOR MONITORING THE RIPENING OF BANANAS - Eldas Febrida, Yuri
Laboratory exercises involving carbohydrates tend to be based on classic qualitative analyses employing Benedict’s reagent, Fehling’s solution, polarimetry, etc. We wanted to develop an introductory-level experiment that focused on quantitative carbohydrate analysis, which is the utilization of common foodstuffs to investigate biochemical principles relevant to nutrition. Test Strips method is one of the alternative experiments that can be used for quantitative carbohydrate analysis at introductory-level experiment. The advantages of this method are the result can be obtained within the short time, cheap and save. We used this method to monitor the ripening of bananas based on the measurement of glucose concentration. Bananas used in our work were divided into two groups, namely the bananas which are consumed directly and the bananas which are consumed after being processed. There are four kinds of bananas used in the experiment: pisang ambon, pisang kapas, pisang muli and pisang nangka. Each of them consisted of five bananas derived from different stem. Initially all bananas were choped into smaller pieces and disolved it into certain volume. Their glucose concentration then were measured by immersed the urine test strips into the solution. Glucose concentration was determined visually by comparing the color developed on the immersed test strips with the reference color. The result showed that glucose concentration in bananas increases following its ripeness.